Dynamics of Computer-Mediated Communication in Digital Health Services: A Qualitative Study on the Alodokter and Halodoc Applications - Galih Primanda Permana; Wulandari Wurjanti; Irwansyah Irwansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study examined the dynamics of computer-mediated communication in digital health services through a comparative analysis of the Alodokter and Halodoc applications in Indonesia. Conceptually, the study is anchored in Computer-Mediated Communication (CMC) and User-Centered Design (UCD) to interpret how interaction patterns and interface choices shape doctor–patient sense-making on mHealth platforms. A qualitative design was employed, using non-participant observation, in-depth interviews, and document analysis. Data were analyzed through open, axial, and selective coding, followed by thematic interpretation. We conducted in-depth interviews with two doctors and two patients, providing an on-the-ground view of how clinicians and users communicate and coordinate care across the two platforms. The findings cluster into three themes: (1) doctors’ flexibility and constraints, including diagnostic limits in the absence of physical examination and work/ incentive trade-offs; (2) patients’ communication experiences, emphasizing accessibility, trust, and privacy; and (3) the role of mobile-AI in facilitating adaptive interactions. Overall, Alodokter and Halodoc enhanced efficiency, reduced time and cost, and expanded access, while face-to-face interaction remained important for complex cases. We conclude that these applications function not only as digital service providers but also as communication ecosystems that shape emerging relationships between healthcare providers and users.